Hi Xia Thanks for the reply! Sorry, maybe i did not explain the whole process from the beginning. My original Y variable has been transformed, first by taking the natural logarithm of Y and then by first differencing; that is taking the first difference between Ln_Yt and Ln_Yt-1 which comes to the dependent variable I actually forecast in my case (i.e. Diff_Ln_Y), using a simple regression. (The reason I'm doing this is to bring my variables to a stationary state so as to meet some of the requirements of OLS). Once I perform the forecasts for the period Q1 16 to Q4 18, I need to back trasform this figure to the original Y value. So for example, for Q1 16 I predict Diff_Ln_Y = 0.056. What I need now is Ln_Y_Q1_16 so as to back transform this to Y using its exponent. Given that Diff_Ln_Y_Q1 16 = Ln Y_Q1_16 - Ln Y_Q4_15 => Ln Y_Q1_16 = Diff_Ln_Y_Q1 16 + Ln Y_Q4_15 Ln Y_Q1_16 = 0.056 + 1.56 = 1.616 The same procedure needs to be applied for Q2 16 and so on. That is, Ln Y_Q2_16 = Diff_Ln_Y_Q2 16 + Ln Y_Q1_16 (this is the figure already calculated above) Ln Y_Q2_16 = 0.057 + 1.616 = 1.673 I hope that this cleared things up a bit more. Thanks!

... View more